2019
DOI: 10.1136/bmjopen-2019-029187
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre randomised feasibility STUdy evaluating the impact of a prognostic model for Management of BLunt chest wall trauma patients: STUMBL Trial

Abstract: ObjectiveA new prognostic model has been developed and externally validated, the aim of which is to assist in the management of the blunt chest wall trauma patient in the emergency department (ED). The aim of this trial is to assess the feasibility and acceptability of a definitive impact trial investigating the clinical and cost-effectiveness of a new prognostic model for the management of patients with blunt chest wall trauma in the ED.DesignStepped wedge feasibility trial.SettingFour EDs in England and Wale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Through a process of constant comparison these were further reduced to 9 themes: five process themes of study design; consent, collecting data; twitter and training were identified alongside two impact themes of making care decisions and reflective practice and finally two themes of looking to the future: mainstreaming and clinical need. Much of these data are presented in the results papers, which also considers possible improvements to the study design [17].…”
Section: Resultsmentioning
confidence: 99%
“…Through a process of constant comparison these were further reduced to 9 themes: five process themes of study design; consent, collecting data; twitter and training were identified alongside two impact themes of making care decisions and reflective practice and finally two themes of looking to the future: mainstreaming and clinical need. Much of these data are presented in the results papers, which also considers possible improvements to the study design [17].…”
Section: Resultsmentioning
confidence: 99%
“…The median age of this patient cohort was greater than that of some of our previous chest trauma trials with the same cohort. [12,13] The five eligible patients who were approached by the physiotherapy team, but declined to participate in the trial, were all younger than 30 years. This would have influenced the median age of participants.…”
Section: Discussionmentioning
confidence: 99%
“…We will determine the intervention costs associated with the exercise programme (which will be minimal as only one sheet of A4 paper), but more focused on the opportunity costs of staff time associated with training and delivery, through data collected during the trial and informant discussions with the project team. We will use the adapted Client Services Receipt Inventory (CSRI) developed from our previous STUMBL feasibility study in the same patient populations 10. Our clinicians and Patient and public involvement (PPI) will review the CSRI to ensure the content and format (eg, time-frame) is accurate for use in the ELECT trial.…”
Section: Methodsmentioning
confidence: 99%
“…We will use the adapted Client Services Receipt Inventory (CSRI) developed from our previous STUMBL feasibility study in the same patient populations. 10 Our clinicians and Patient and public involvement (PPI) will review the CSRI to ensure the content and format (eg, time-frame) is accurate for use in the ELECT trial. We will collect participant level health and social resource use in both the intervention and control (usual care) groups using the adapted CSRI at 3 months.…”
Section: Methodsmentioning
confidence: 99%